Pengaruh Kepemimpinan, Profesionalisme Dan Motivasi Terhadap Kinerja Guru - Tarjuni Tarjuni; Syahrosi Syahrosi; Nicomedis Nicomedis (E-Journal Studia Manajemen, 2022)
This study aims to examine leadership, professionalism and motivation on teacher performance. The research method is a quantitative-descriptive method. Analysis of the data used is multiple regression using the SPSS program. The research population was 994 MTs teachers in South Tangerang City, then 285 were used as samples. The results obtained: (1) there is an influence, the leadership variable X1 on teacher Y performance, which is indicated by the t-count value of 2,429 with t- the table is 1.984 which is smaller than the 0.05 significance level, (2) there is an effect of the professionalism variable X2 on the teacher's performance Y which is indicated by the t-count value of 4.756 with a t-table of 1.985 which is smaller than the 0.05 significance level, (3) there is an effect of work motivation X3 on the performance of teacher Y which is indicated by the t-count value of 5.923 with a t-table of 1.985 which is smaller than the 0.05 level of significance, and (4) there is a significant influence on leadership X1, professionalism X2 , and the work motivation of X3 simultaneously on the performance of teacher Y as indicated by the F-count value of 77.570 and F-table 3 .090 (Sig.) of 0.000 at a significance level of 0.05. The implication of this research is to keep the value of Y in a safe and good condition, the parties must continue to manage so that the values of X1, X2, and X3 are in good values as well.